A self-compacting high crack resistance desert sand fiber concrete material and preparation method thereof
By modifying desert sand and alkali-resistant glass fiber, self-dense and highly crack-resistant desert sand fiber concrete is prepared, which solves the problems of concrete strength and crack resistance when desert sand replaces river sand, and achieves efficient and environmentally friendly concrete preparation.
Patent Information
- Application Number
- CN202411426093.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-14
AI Technical Summary
How to use desert sand instead of river sand to prepare self-condensed concrete and ensure that it has better crack resistance, solves the problem of the reduction in concrete strength and high water absorption when desert sand replaces river sand in large quantities.
By modifying desert sand and alkali-resistant glass fiber, self-compacting concrete is prepared using modified desert sand and modified alkali-resistant glass fiber to improve the interface bonding strength and thereby improve the crack resistance of concrete.
The preparation of the dense high -cranched desert sand fiber concrete is realized, the crack resistance and strength of the concrete is improved, the mining of river sand is reduced, the cost is reduced, the environment is protected, and resources are saved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of concrete materials, and in particular to a self-compacting high-cracking-resistant desert sand fiber concrete material and a preparation method thereof. Background Art
[0002] With the increase in infrastructure construction, the demand for building materials has also shown a sharp growth trend. At present, the production speed of river sand is extremely slow, while the consumption speed is too fast. Especially in recent years, the global urbanization has developed rapidly. River sand is used in building buildings, bridges, roads, etc., resulting in an increasing demand for sand every year, which has led to a shortage of sand. There is a large gap in river sand, and the excessive exploitation of river sand has extremely bad effects on the environment, including dust, overall riverbed cutting, dam foundation collapse and flooding. Desert sand is the broken product of rocks after physical action and chemical erosion. The sand particles are mostly round and have a relatively smooth surface. The particles are small (fineness modulus is 1.5-0.2) and the gradation is relatively simple. China has a vast desert area of about 700,000 km 2 , mainly distributed in the vast western region, especially Xinjiang. Desert sand can just solve the problem of river sand shortage.
[0003] Desert sand is a very fine sand resource with high water absorption rate. If it is used to replace river sand in large quantities, the strength of concrete will be reduced and the slump performance will not meet the requirements. Secondly, desert sand concrete has extremely high water absorption rate and the concrete paste has poor fluidity. In addition, desert sand may contain harmful substances such as soluble salts and clay. If it is not treated before use, it will affect the strength of concrete. The Chinese invention patent with publication number CN112250375A discloses a desert sand concrete and a desert sand concrete composite column. The invention study found that when the sand in the concrete is replaced only with desert sand, the compressive strength decreases slightly and the tensile strength is almost unaffected. When waste glass is used to replace river sand, the compressive strength of the concrete is improved compared with the situation when there is no desert sand replacement and when there is desert sand replacement. This is because the addition of waste glass powder makes the concrete more compact during vibration and the tensile strength is significantly improved. Desert sand can greatly improve the fluidity of concrete, which is manifested as an increase in slump. Since waste glass powder is used as fine aggregate to replace river sand, it will reduce the fluidity of concrete, which to a certain extent reduces the slump of concrete added by desert sand. This invention uses waste glass to replace river sand to make up for the shortcomings of desert sand. However, the method used in this invention is not suitable for preparing self-compacting concrete.
[0004] Self-compacting concrete is able to flow and compact under its own gravity, while achieving good homogeneity and being able to fill any gaps in the formwork through dense steel bars. The characteristics of this concrete make it unnecessary to vibrate during construction, thus simplifying the construction process and improving construction efficiency. Compared with traditional compacted concrete, self-compacting high crack-resistant desert sand fiber concrete has the advantages of high strength and large elastic modulus, and has integrity after solidification, which can not only improve the construction speed and mechanization level, but also because of its high strength and large deformation modulus, it is suitable for a variety of engineering applications, such as rapid highway widening, pipeline corridor backfill, rapid backfill of bridge abutments, and high slope integral roadbed.
[0005] The Chinese invention with publication number CN118047572A discloses a high-fluidity self-compacting concrete and a preparation method thereof. By using a sensitivity modifier, the prepared self-compacting concrete has the technical advantages of good fluidity, strong volume stability, low water sensitivity, long fluidity retention time, small thixotropic change over time, and low shrinkage. However, the high-fluidity self-compacting concrete does not have crack resistance.
[0006] The Chinese invention patent with publication number CN117447139A discloses a self-compacting concrete and a preparation method thereof. The prepared concrete not only has outstanding fluidity and anti-segregation performance, but also has excellent elastic modulus and compactness. However, since glass fiber is usually rigid and polypropylene fiber is relatively soft, this may result in a certain degree of limitation in the plasticity of concrete, especially in applications that require high plasticity. In addition, polypropylene fiber has a low melting point, which means that it may melt in a high temperature environment, thereby reducing the crack resistance of concrete.
[0007] There is little research on modifying desert sand and using it to prepare self-compacting concrete. How to use desert sand instead of river sand to prepare self-compacting concrete and ensure that it has better crack resistance is a technical problem that needs to be solved in this field. Summary of the invention
[0008] The purpose of the present invention is to provide a self-compacting high crack-resistant desert sand fiber concrete material and a preparation method thereof in view of the above-mentioned problems. The present invention modifies desert sand and alkali-resistant glass fiber for use in preparing self-compacting concrete, thereby improving the interfacial bonding strength and thus the strength of the self-compacting concrete. The use of desert sand can effectively reduce the mining of river sand, reduce costs, protect the environment and save resources, and can also enable the rational development of desert sand resources and the reuse of waste materials.
[0009] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A self-compacting high crack-resistant desert sand fiber concrete is made from the following raw materials in parts by weight:
[0011] 210-240 parts of cement, 70-90 parts of fly ash, 115-130 parts of water, 60-70 parts of modified desert sand, 5-10 parts of modified alkali-resistant glass fiber, 120-140 parts of river sand, 220-260 parts of coarse aggregate, 10-20 parts of steel balls, 5 parts of xanthan gum, 10 parts of water reducer, water-cement ratio is 0.35-0.40;
[0012] The modified alkali-resistant glass fiber is obtained by the following preparation process:
[0013] ① At room temperature, immerse the alkali-resistant glass fiber in a silane solution for 20-60 minutes to treat the surface of the alkali-resistant glass fiber; the silane solution is a mixed solution of 3 parts of isooctylisobutyltriethoxysilane and 1 part of distilled water by weight;
[0014] ②After draining the silane solution, rinse the alkali-resistant glass fiber with water several times to remove the residual silane and dissolved impurities;
[0015] ③ Dry the washed alkali-resistant glass fiber to remove excess water, thereby obtaining modified alkali-resistant glass fiber;
[0016] The modified desert sand is obtained by the following preparation process:
[0017] ① At room temperature, wash the desert sand with anhydrous ethanol to remove impurities;
[0018] ② Soak the desert sand in 3 parts of silane coupling agent solution for 2-4 hours;
[0019] ③ Soak the desert sand in the silicone resin solution for 10-15 hours and wait for the desert sand surface modifier to cure naturally under laboratory conditions.
[0020] In the present invention, preferably, the silane coupling agent solution is γ-aminopropyltrimethoxysilane.
[0021] In the present invention, preferably, the organic silicone resin is methylphenyl polysiloxane resin.
[0022] In the present invention, preferably, the fineness modulus of the desert sand is less than 0.6; and the fineness modulus of the river sand is 2.9-3.7.
[0023] In the present invention, preferably, the coarse aggregate is artificial crushed stone with a particle size range of 5-25 mm; wherein, large stone and small stone are used in a mass ratio of 835-840:365-380, large stone refers to artificial crushed stone with a particle size range of 10-25 mm, and small stone refers to artificial crushed stone with a particle size range of 5-10 mm.
[0024] In the present invention, preferably, the cement is selected from rapid hardening Portland cement.
[0025] In the present invention, preferably, the alkali-resistant glass fiber is a bundle of monofilaments with a length of 11-13 mm, a tensile strength of ≥1600 MPa, and an elastic modulus of ≥40 GPa.
[0026] In the present invention, preferably, the water reducer is a polycarboxylic acid high-efficiency powder water reducer.
[0027] In the present invention, preferably, the steel ball has a particle size of 7-8 mm and an apparent density of 7000-7500 kg / m 3 .
[0028] The method for preparing self-compacting high crack-resistant desert sand fiber concrete is characterized by comprising the following steps:
[0029] (1) Place the river sand and coarse aggregate weighed by weight in a mixer and slowly dry mix them to ensure that the dry materials are evenly mixed and soaked;
[0030] (2) Add all the cement, fly ash and modified desert sand into the mixer and continue to stir at a slow speed;
[0031] (3) Add the prepared water reducer and remaining water and continue stirring slowly;
[0032] (4) After stirring evenly, add xanthan gum and steel balls and continue stirring slowly;
[0033] (5) Add the modified alkali-resistant glass fiber into the mixer in batches and stir quickly to make the fiber dispersed evenly and avoid agglomeration;
[0034] (6) Pour the mixed slurry into the mold, let it stand for 2-3 hours, and then seal it with plastic film. After demolding, continue to cure at room temperature for up to 28 days.
[0035] In the present invention, alkali-resistant glass fiber is a reinforcing fiber processed and manufactured by a unique production process. It can effectively control the micro cracks caused by factors such as plastic shrinkage, drying shrinkage, temperature, humidity, etc. of concrete or cement mortar, prevent the generation of cracks and effectively inhibit the expansion of cracks, greatly improve and enhance the comprehensive ability of concrete to resist penetration, impact load, chemical erosion, high-speed water flow and abrasion of bedload, and extend the service life of the structure. However, due to its smooth surface, alkali-resistant glass fiber will lead to poor bonding performance between it and concrete. By modifying the surface of alkali-resistant glass fiber with silane coupling agent and silicone resin, its surface chemistry and roughness can be improved, and the interface bonding with cement-based slurry can be improved, thereby improving the crack resistance of concrete.
[0036] In addition, by modifying the desert sand, the pores and grooves on the surface of the desert sand are filled and covered by the modifier, thereby increasing the wetting angle of the desert sand, reducing its surface absorption capacity for water in the cement paste, ensuring the demand for water during the hardening process of the cement paste, and improving the hydration quality of the cement stone at the interface, thereby increasing the interfacial bonding strength and improving the crack resistance of the concrete.
[0037] The present invention can make concrete more compact by adding xanthan gum and steel balls. Xanthan gum solution has the characteristics of low concentration and high viscosity, can significantly improve the water retention and workability of concrete, and has a good suspension effect on insoluble solids and oil droplets, can support the morphology of solid particles, droplets and bubbles, and shows a strong emulsification stabilization effect and high suspension ability, which is very important for improving the crack resistance of concrete. By adding steel balls, the pores in the concrete can also be filled, so that the density of the concrete is improved; the steel balls can also increase the toughness and tensile strength of the concrete, thereby improving the overall compressive strength of the concrete; the addition of steel balls can disperse and relieve the stress of the concrete, increase its ductility and toughness, which is also one of the main functions of adding steel balls in concrete.
[0038] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0039] 1. The present invention can improve the surface chemistry and roughness of alkali-resistant glass fiber by modifying the surface, improve the interface bonding with cement-based slurry, and thus improve the crack resistance of concrete; by modifying desert sand, the pores and grooves on the surface of desert sand are filled and covered by the modifier, thereby increasing the wetting angle of desert sand, reducing its surface absorption capacity for water in cement slurry, ensuring the demand for water during the hardening process of cement slurry, improving the hydration quality of cement stone at the interface, and then improving the interfacial bonding strength. The present invention can also make concrete more compact by adding xanthan gum and steel balls, thereby improving the fluidity of concrete. The present invention uses desert sand instead of river sand to prepare self-compacting concrete through the mutual cooperation of multiple factors, and ensures that it has better crack resistance.
[0040] 2. The utilization of desert sand by the present invention can effectively reduce the exploitation of river sand, reduce costs, protect the environment and save resources, and can also enable the rational development of desert sand resources and the recycling of waste materials.
[0041] 3. The present invention prepares self-compacting and crack-resistant concrete by rationally designing the proportions of cement, river sand, coarse aggregate, fly ash, water, water reducing agent, modified alkali-resistant glass fiber, modified desert sand, xanthan gum and steel balls. The concrete can flow and compact under the action of its own gravity, thus solving the problem of external vibration required in traditional concrete construction. DETAILED DESCRIPTION
[0042] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0043] In the embodiment of the present invention, cement is selected from P·O42.5 cement; fly ash is selected from first-class fly ash; xanthan gum is selected from xanthan gum produced by Zhonglian Chemical Specimen Co., Ltd.; silane solution is selected from isooctyl isobutyl triethoxy solution produced by Tianjin Jiuyan New Material Technology Co., Ltd.; silane coupling agent solution is selected from γ-aminopropyl trimethoxy silane, produced by Nanjing Pinning Coupling Agent Co., Ltd., model silane coupling agent KH-792; silicone resin is selected from 1053 silicone resin (methylphenyl polysiloxane resin) produced by Jining Tangyi Chemical Co., Ltd.; water reducer is purchased from polycarboxylic acid high-efficiency powder water reducer PC-1 of Shanghai Kehong Chemical Co., Ltd., and desert sand comes from the Taklimakan Desert in southern Xinjiang.
[0044] Unless otherwise specified, the raw materials used in the examples are all well-known, commercially available chemical raw materials.
[0045] Example 1
[0046] A self-compacting high crack-resistant desert sand fiber concrete is made from the following raw materials in parts by weight:
[0047] 210kg of rapid-hardening silicate cement, 70kg of fly ash, 110kg of water, 60kg of modified desert sand, 6kg of modified alkali-resistant glass fiber, 140kg of river sand, 256kg of coarse aggregate, 10kg of steel balls, 5kg of xanthan gum, and 10kg of polycarboxylic acid high-efficiency powder water reducer; among them, the fineness modulus of desert sand is less than 0.6; the fineness modulus of river sand is 2.9-3.7; the coarse aggregate is artificial crushed stone with a particle size range of 5-25mm; including large stones and small stones with a mass ratio of 835:365, large stones refer to artificial crushed stones with a particle size range of 10-25mm, and small stones refer to artificial crushed stones with a particle size range of 5-10mm; the steel balls have a particle size of 7-8mm and an apparent density of 7000-7500kg / m 3 ;
[0048] A method for preparing self-compacting highly crack-resistant desert sand fiber concrete is as follows:
[0049] (1) Modification of alkali-resistant glass fiber:
[0050] ① At room temperature, alkali-resistant glass fiber is immersed in silane solution for 20 minutes to treat the surface of alkali-resistant glass fiber; the silane solution is a mixed solution of 3kg isooctylisobutyltriethoxysilane and 1kg distilled water; the alkali-resistant glass fiber is a bundled monofilament with a length of 11-13mm, a tensile strength of ≥1600MPa, and an elastic modulus of ≥40GPa;
[0051] ②After draining the silane solution, rinse the alkali-resistant glass fiber with water several times to remove the residual silane and dissolved impurities;
[0052] ③ Dry the washed alkali-resistant glass fiber at 90-100°C for 24 hours to remove excess water, thereby obtaining modified alkali-resistant glass fiber;
[0053] (2) Modification of desert sand:
[0054] ① At room temperature, wash the desert sand with anhydrous ethanol to remove impurities;
[0055] ② Soak the desert sand in 3kg γ-aminopropyltrimethoxysilane solution for 2h;
[0056] ③ Soak the desert sand in the methylphenyl polysiloxane resin solution for 10 hours, and wait for the desert sand surface modifier to cure naturally under laboratory conditions;
[0057] (3) Preparation of self-compacting high crack resistance desert sand fiber concrete:
[0058] ①Put the river sand and coarse aggregate weighed by weight into a mixer and slowly dry mix them to make the dry materials evenly mixed and soaked;
[0059] ② Add all the cement, fly ash and modified desert sand into the mixer and continue to stir slowly;
[0060] ③ Add the prepared water reducer and remaining water and continue stirring slowly;
[0061] ④After stirring evenly, add xanthan gum and steel balls and continue stirring slowly;
[0062] ⑤ Add the modified alkali-resistant glass fiber into the mixer in batches and stir quickly to make the fiber dispersed evenly and avoid agglomeration;
[0063] ⑥ Pour the mixed slurry into the mold, let it stand for 2 hours, then seal it with plastic film. After demoulding, continue to cure at room temperature for up to 28 days.
[0064] Example 2
[0065] A self-compacting high crack resistance desert sand fiber concrete made from the following raw materials by weight:
[0066] 225kg of rapid-hardening silicate cement, 80kg of fly ash, 120kg of water, 65kg of modified desert sand, 10kg of modified alkali-resistant glass fiber, 140kg of river sand, 260kg of coarse aggregate, 13kg of steel balls, 5kg of xanthan gum, and 10kg of polycarboxylic acid high-efficiency powder water reducer; among them, the fineness modulus of desert sand is less than 0.6; the fineness modulus of river sand is 2.9-3.7; the coarse aggregate is artificial crushed stone with a particle size range of 5-25mm; including large stones and small stones with a mass ratio of 840:380, large stones refer to artificial crushed stones with a particle size range of 10-25mm, and small stones refer to artificial crushed stones with a particle size range of 5-10mm; the steel balls have a particle size of 7-8mm and an apparent density of 7000-7500kg / m 3 ;
[0067] A method for preparing self-compacting highly crack-resistant desert sand fiber concrete is as follows:
[0068] (1) Modification of alkali-resistant glass fiber:
[0069] ① At room temperature, alkali-resistant glass fiber is immersed in silane solution for 30 minutes to treat the surface of alkali-resistant glass fiber; the silane solution is a mixed solution of 3kg isooctylisobutyltriethoxysilane and 1kg distilled water; the alkali-resistant glass fiber is a bundled monofilament with a length of 11-13mm, a tensile strength of ≥1600MPa, and an elastic modulus of ≥40GPa;
[0070] ②After draining the silane solution, rinse the alkali-resistant glass fiber with water several times to remove the residual silane and dissolved impurities;
[0071] ③ Dry the washed alkali-resistant glass fiber at 90-100°C for 24 hours to remove excess water, thereby obtaining modified alkali-resistant glass fiber;
[0072] (2) Modification of desert sand:
[0073] ① At room temperature, wash the desert sand with anhydrous ethanol to remove impurities;
[0074] ② Soak the desert sand in 3kg γ-aminopropyltrimethoxysilane solution for 3h;
[0075] ③ Soak the desert sand in the methylphenyl polysiloxane resin solution for 12 hours, and wait for the desert sand surface modifier to cure naturally under laboratory conditions;
[0076] (3) Preparation of self-compacting high crack resistance desert sand fiber concrete:
[0077] ①Put the river sand and coarse aggregate weighed by weight into a mixer and slowly dry mix them to make the dry materials evenly mixed and soaked;
[0078] ② Add all the cement, fly ash and modified desert sand into the mixer and continue to stir slowly;
[0079] ③ Add the prepared water reducer and remaining water and continue stirring slowly;
[0080] ④After stirring evenly, add xanthan gum and steel balls and continue stirring slowly;
[0081] ⑤ Add the modified alkali-resistant glass fiber into the mixer in batches and stir quickly to make the fiber dispersed evenly and avoid agglomeration;
[0082] ⑥ Pour the mixed slurry into the mold, let it stand for 3 hours, then seal it with plastic film. After demoulding, continue to cure at room temperature for up to 28 days.
[0083] Example 3
[0084] A self-compacting high crack resistance desert sand fiber concrete made from the following raw materials by weight:
[0085] 240kg of rapid-hardening silicate cement, 90kg of fly ash, 130kg of water, 70kg of modified desert sand, 8kg of modified alkali-resistant glass fiber, 140kg of river sand, 255kg of coarse aggregate, 15kg of steel balls, 5kg of xanthan gum, and 10kg of polycarboxylic acid high-efficiency powder water reducer; among them, the fineness modulus of desert sand is less than 0.6; the fineness modulus of river sand is 2.9-3.7; the coarse aggregate is artificial crushed stone with a particle size range of 5-25mm; including large stones and small stones with a mass ratio of 835:380, large stones refer to artificial crushed stones with a particle size range of 10-25mm, and small stones refer to artificial crushed stones with a particle size range of 5-10mm; the steel balls have a particle size of 7-8mm and an apparent density of 7000-7500kg / m 3 ;
[0086] A method for preparing self-compacting highly crack-resistant desert sand fiber concrete is as follows:
[0087] (1) Modification of alkali-resistant glass fiber:
[0088] ① At room temperature, alkali-resistant glass fiber is immersed in silane solution for 60 minutes to treat the surface of alkali-resistant glass fiber; the silane solution is a mixed solution of 3kg isooctylisobutyltriethoxysilane and 1kg distilled water; the alkali-resistant glass fiber is a bundled monofilament with a length of 11-13mm, a tensile strength of ≥1600MPa, and an elastic modulus of ≥40GPa;
[0089] ②After draining the silane solution, rinse the alkali-resistant glass fiber with water several times to remove the residual silane and dissolved impurities;
[0090] ③ Dry the washed alkali-resistant glass fiber at 90-100°C for 24 hours to remove excess water, thereby obtaining modified alkali-resistant glass fiber;
[0091] (2) Modification of desert sand:
[0092] ① At room temperature, wash the desert sand with anhydrous ethanol to remove impurities;
[0093] ② Soak the desert sand in 3kg γ-aminopropyltrimethoxysilane solution for 4h;
[0094] ③ Soak the desert sand in the methylphenyl polysiloxane resin solution for 15 hours, and wait for the desert sand surface modifier to cure naturally under laboratory conditions;
[0095] (3) Preparation of self-compacting high crack resistance desert sand fiber concrete:
[0096] ①Put the river sand and coarse aggregate weighed by weight into a mixer and slowly dry mix them to make the dry materials evenly mixed and soaked;
[0097] ② Add all the cement, fly ash and modified desert sand into the mixer and continue to stir slowly;
[0098] ③ Add the prepared water reducer and remaining water and continue stirring slowly;
[0099] ④After stirring evenly, add xanthan gum and steel balls and continue stirring slowly;
[0100] ⑤ Add the modified alkali-resistant glass fiber into the mixer in batches and stir quickly to make the fiber dispersed evenly and avoid agglomeration;
[0101] ⑥ Pour the mixed slurry into the mold, let it stand for 3 hours, then seal it with plastic film. After demoulding, continue to cure at room temperature for up to 28 days.
[0102] Comparative Example 1
[0103] The only difference between this comparative example and Example 2 is that the desert sand is not modified, that is, there is no step of modifying the desert sand, and the other raw materials and steps are the same as those in Example 2.
[0104] Comparative Example 2
[0105] The only difference between this comparative example and Example 2 is that the alkali-resistant glass fiber is not modified, that is, there is no step of modifying the alkali-resistant glass fiber, and the other raw materials and steps are the same as those in Example 2.
[0106] Comparative Example 3
[0107] The difference between this comparative example and Example 2 is that the modification method of desert sand is different, specifically:
[0108] ① At room temperature, wash the desert sand with anhydrous ethanol to remove impurities;
[0109] ② Soak the desert sand in 3kg γ-aminopropyltrimethoxysilane solution for 3h;
[0110] ③ Wait for the desert sand surface modifier to solidify naturally under laboratory conditions.
[0111] That is, the modification of desert sand does not include the step of soaking in the methylphenyl polysiloxane resin solution, and the other raw materials and steps are the same as those in Example 2.
[0112] Comparative Example 4
[0113] The only difference between this comparative example and Example 2 is that an equal amount of small stones are used instead of steel balls, and other raw materials and steps are the same as those in Example 2.
[0114] Comparative Example 5
[0115] The only difference between this comparative example and Example 2 is that the amount of modified desert sand is 80 kg, the amount of river sand is 125 kg, and the other raw materials and steps are the same as those in Example 2.
[0116] The concrete prepared in the examples and comparative examples was subjected to performance tests, including slump expansion, compressive strength, and splitting tensile strength. The results are recorded in Table 1.
[0117] The test method is as follows:
[0118] Slump and spread: To test the working performance of concrete slump and spread, an inverted slump cone with a cover fixed to the bottom of the cone is placed 50 cm above the ground. The cone is filled with concrete and smoothed. The bottom cover is quickly slid open and the flow time is measured with a stopwatch. The concrete flow diameter (slump and spread) and the height difference between the middle and the edge (center-edge difference) are measured in combination with the slump measurement.
[0119] Compressive strength: The compressive strength on the 28th day was tested according to the method in Appendix C of JGJ / T 372-2016 “Technical Code for Application of Low-cost Shotcrete”.
[0120] Split tensile strength: Split tensile test is carried out in accordance with GB / T50081 "Standard for test methods of mechanical properties of ordinary concrete".
[0121] Table 1 Performance test results
[0122]
[0123] As can be seen from Table 1, the fluidity and compressive properties of Comparative Examples 1 and 3 are poor, indicating that direct addition of desert sand without modification or different modification methods will lead to reduced compressive properties and fluidity of concrete; the crack resistance of Comparative Example 2 is low, indicating that unmodified alkali-resistant glass fiber will make the crack resistance of concrete poor; in Comparative Example 4, steel balls are replaced by pebbles, and the results show that the compressive properties of concrete are deteriorated; it can be seen from Comparative Example 5 that when the amount of modified desert sand is increased, the fluidity of concrete increases slightly, but the compressive strength decreases significantly.
[0124] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A self-compacting high crack resistance desert sand fiber concrete, characterized in that: Made from the following raw materials in parts by weight: 210-240 parts of cement, 70-90 parts of fly ash, 110-130 parts of water, 60-70 parts of modified desert sand, 6-10 parts of modified alkali-resistant glass fiber, 140 parts of river sand, 255-260 parts of coarse aggregate, 10-20 parts of steel balls, 5 parts of xanthan gum, 10 parts of water reducer, water-cement ratio is 0.35-0.40; The modified alkali-resistant glass fiber is obtained by the following preparation process: ① At room temperature, immerse the alkali-resistant glass fiber in a silane solution for 20-60 minutes to treat the surface of the alkali-resistant glass fiber; the silane solution is a mixed solution of 3 parts of isooctylisobutyltriethoxysilane and 1 part of distilled water by weight; ②After draining the silane solution, rinse the alkali-resistant glass fiber with water several times to remove the residual silane and dissolved impurities; ③ Dry the washed alkali-resistant glass fiber to remove excess water, thereby obtaining modified alkali-resistant glass fiber; The modified desert sand is obtained by the following preparation process: ① At room temperature, wash the desert sand with anhydrous ethanol to remove impurities; ② Soak the desert sand in 3 parts of silane coupling agent solution for 2-4 hours; the silane coupling agent solution is γ-aminopropyltrimethoxysilane; ③ Soak the desert sand in a silicone resin solution for 10-15 hours, and allow the surface modifier of the desert sand to cure naturally under laboratory conditions. The silicone resin is methylphenyl polysiloxane resin.
2. The self-compacting high crack resistance desert sand fiber concrete according to claim 1, characterized in that: The fineness modulus of the desert sand is less than 0.6; the fineness modulus of the river sand is 2.9-3.
7.
3. The self-compacting high crack resistance desert sand fiber concrete according to claim 1, characterized in that: The coarse aggregate is artificial crushed stone with a particle size range of 5-25mm; wherein the mass ratio of large stone and small stone is 835-840:365-380, the large stone refers to the artificial crushed stone with a particle size range of 10-25mm, and the small stone refers to the artificial crushed stone with a particle size range of 5-10mm.
4. The self-compacting high crack resistance desert sand fiber concrete according to claim 1, characterized in that: The cement is selected from rapid hardening Portland cement.
5. The self-compacting high crack resistance desert sand fiber concrete according to claim 1, characterized in that: The alkali-resistant glass fiber is a bundle of monofilaments with a length of 11-13 mm, a tensile strength of ≥1600 MPa, and an elastic modulus of ≥40 GPa.
6. The self-compacting high crack resistance desert sand fiber concrete according to claim 1, characterized in that: The water reducer is a polycarboxylic acid high-efficiency powder water reducer.
7. The self-compacting high crack resistance desert sand fiber concrete according to claim 1, characterized in that: The steel balls have a particle size of 7-8 mm and an apparent density of 7000-7500 kg / m 3 .
8. The method for preparing the self-compacting high crack resistance desert sand fiber concrete according to any one of claims 1 to 7, characterized in that: The steps include: (1) Place river sand and coarse aggregate weighed by weight in a mixer and slowly dry mix them to ensure that the dry materials are evenly mixed and soaked; (2) Add all the cement, fly ash and modified desert sand into the mixer and continue to stir slowly; (3) Add the prepared water reducer and remaining water and continue stirring slowly; (4) After stirring evenly, add xanthan gum and steel balls and continue stirring slowly; (5) Add the modified alkali-resistant glass fibers into a mixer in batches and stir quickly to ensure that the fibers are evenly dispersed and avoid agglomeration; (6) Pour the stirred slurry into a mold, let it stand for 2-3 hours, then seal it with a plastic film. After demolding, continue to cure it at room temperature for up to 28 days.
Citation Information
Patent Citations
Desert sand concrete and desert sand concrete combined column
CN112250375A
Self-compacting concrete and preparation method thereof
CN117447139A
High-fluidity self-compacting concrete as well as preparation method and application thereof
CN118047572A
C60 concrete by using desert sands for substituting sands used for steel pipe concrete
CN106116340A
Desert aeolian sand high-ductility cement-based composite material and preparation method thereof
CN114634338A